2008
DOI: 10.1097/aco.0b013e3282f35ebf
|View full text |Cite
|
Sign up to set email alerts
|

Hemodilution and anemia in patients with cardiac disease: what is the safe limit?

Abstract: The absolute lowest threshold for anemia in patients with cardiac disease cannot be established. Further studies are needed to develop evidence-based transfusion guidelines for these patients. Rather than primarily focusing on transfusion, physicians should first administer therapies that have been shown to improve outcome. In the setting of coronary artery disease, control of heart rate appears of paramount importance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…It is established that during acute myocardial ischemia, myocardial injury becomes worse by concomitant anemia 3 and there is a resultant worsening of such patients’ prognosis. 4 Nevertheless, it is unknown what should be the absolute threshold for giving blood transfusions to patients suffering from chronic ischemic heart disease (IHD) and anemia 5 nor it is known what should be the threshold for administrating blood transfusions for patients with acute coronary syndromes (ACSs). 6 Moreover, it was shown that restrictive blood transfusion strategies, limiting such treatment, in a population of critically ill patients (including patients suffering from cardiac events) to levels of hemoglobin which were lower than 7 g/L had better clinical results.…”
Section: Introductionmentioning
confidence: 99%
“…It is established that during acute myocardial ischemia, myocardial injury becomes worse by concomitant anemia 3 and there is a resultant worsening of such patients’ prognosis. 4 Nevertheless, it is unknown what should be the absolute threshold for giving blood transfusions to patients suffering from chronic ischemic heart disease (IHD) and anemia 5 nor it is known what should be the threshold for administrating blood transfusions for patients with acute coronary syndromes (ACSs). 6 Moreover, it was shown that restrictive blood transfusion strategies, limiting such treatment, in a population of critically ill patients (including patients suffering from cardiac events) to levels of hemoglobin which were lower than 7 g/L had better clinical results.…”
Section: Introductionmentioning
confidence: 99%
“…In conscious humans it has been shown that the increase in cardiac output and in the oxygen extraction rate has successfully preserved the adequate supply of tissue oxygen until Hb reaches 5.0 g/dL . Extraction rates of oxygen vary for different organs and systems; therefore, it cannot be substantiated that a global measure like oxygen delivery would reflect upon the necessity and adequacy of perfusion . Some related cases of patients who survived levels of Hb below 2.0 g/dL are clinical proof of this fact .…”
Section: Discussionmentioning
confidence: 99%
“…These two studies identified Hb levels as low as 5-6 g/dl to be relevant, indicating commonly used triggers like 10 g/dl might not be necessary to provide sufficient oxygen supply. Notably, a recent review article by Tircoveanu and Van der Linden [50 ] could not establish 'the minimal' threshold for anemia in patients with cardiac disease and recommended that, rather than primarily focusing on transfusion, physicians should first administer therapies that have been shown to improve outcome, such as control of heart rate.…”
Section: Transfusion Triggersmentioning
confidence: 98%